Case Report—Escherichia coli Pericarditis after Recent COVID-19 Pneumonia - Xinhang Tu; Nahar Saleh; Raymond Young (Journal of Respiration, 2023)
Before the widespread use of antibiotics, purulent pericarditis was not uncommon and was predominantly a complication of bacterial pneumonia. We present a rare case of Escherichia coli (E. coli) purulent pericarditis without a clear source after a recent COVID-19 infection. Background: COVID-19 has been affecting millions of people worldwide since the outbreak in December 2019, and its involvement in multiple organ systems has been observed and studied. Multiple cardiac complications have been reported, most significantly the virus’ ability to induce acute coronary syndrome and myocarditis. Pericardial disease has also been reported but less frequently. COVID-19 infection is associated with a higher risk of secondary bacterial infection, but it is rare to see purulent pericarditis in the setting of a recent COVID-19 infection. Objective: Our case report depicts a patient who developed E. coli purulent pericarditis in the setting of a recent COVID-19 infection. It indicates a possible association between COVID-19 infection with dysregulation of the immune system.